Cisplatin-Induced Renal Failure Measured by Glomerular Filtration Rate (GFR) with 99mTc-DTPA Scans in Cancer Patients: A Systematic Review and Meta-Analysis - Mansour M. Alqahtani (Diagnostics)
Background: Cisplatin is a potent agent commonly used to treat cancer, but its effects pose a significant risk to renal function. Therefore, the present study aimed to evaluate the impact of cisplatin on renal function as measured by glomerular filtration rate (GFR) using diethyltriamine-penta-acetic acid (DTPA) renal scintigraphy. Methods: Extensive literature searches were performed using PRISMA guidelines that investigated cisplatin-induced renal failure by measuring GFR with DTPA. Eligible studies were included based on predefined criteria. Data on GFR, serum creatinine levels, and acute kidney injury (AKI) before and after cisplatin therapy were extracted and analyzed. A meta-analysis was performed utilizing RevMan 5.4 to determine the overall effect of cisplatin on GFR before and after treatment. For non-randomized controlled trials (RCTs), quality assessment was performed using the Newcastle–Ottawa Scale, while for RCT, the Cochrane risk of bias tool was utilized. Results: Initially, 1003 studies were searched from different databases, including ScienceDirect, PubMed, Scopus, Google Scholar, and The Cochrane Library, and after screening, 8 studies (PubMed, Scopus, and GoogleS cholar) with 489 patients were found eligible for inclusion in the present study. Cisplatin was administrated with varying doses ranging from 20 mg/m2 to 114.02 mg/m2. The findings underscore the nephrotoxic effects of cisplatin, a widely used chemotherapeutic agent, as demonstrated by the significant decline in GFR observed across multiple treatment cycles, and these findings were also supported by the findings of a meta-analysis that showed a significant (p < 0.01) difference between peri- and post-treatment GFR level with 37.06 (95% CI, 10.90–63.23) effect size and 96% heterogeneity. In addition, the included studies were found to be of high quality. Conclusions: Cisplatin significantly affects renal function, as evidenced by a decrease in GFR measured with DTPA. The findings underscore the importance of the routine monitoring of GFR to detect early renal injury and guide treatment modification. Future research should focus on strategies to reduce cisplatin-induced toxicity and explore alternative therapies with reduced renal risk.